1981
DOI: 10.1126/science.6782676
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of Limulus Photoreceptors by Vanadate and by a Hydrolysis-Resistant Analog of Guanosine Triphosphate

Abstract: Discrete voltage fluctuations that occur spontaneously or in response to dim lights can be recorded from the ventral photoreceptors of Limulus. The injection of vanadate or the hydrolysis-resistant analog of guanosine triphosphate, GTP-gamma-S, into ventral photoreceptors induces the production of discrete waves in the dark. The chemically induced discrete waves are similar to those induced by light. Ventral photoreceptors may contain a guanyl nucleotide binding protein whose activation by vanadate or GTP-gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…After injection of this activator into the cell and stimulation of guanine nucleotide exchange by light there was a sustained increase in the frequency of discrete events in the dark, as previously reported for this and other G protein activators (17,31,32). Fig.…”
Section: Resultssupporting
confidence: 61%
“…After injection of this activator into the cell and stimulation of guanine nucleotide exchange by light there was a sustained increase in the frequency of discrete events in the dark, as previously reported for this and other G protein activators (17,31,32). Fig.…”
Section: Resultssupporting
confidence: 61%
“…7E). The variance of this noise was transiently reduced from 0.16 to 0.06 mV 2 after 20 msec flashes of light (log 10 Ϫ4.4) consistent with the adaptation of GTP-␥-Sinduced events (Fein and Corson, 1981). We therefore conclude that desensitization by (Ϫ)-indolactam V is downstream from rhodopsin.…”
Section: (؊)-Indolactam V Inhibits the Phototransduction Cascade At Tmentioning
confidence: 49%
“…Furthermore, for invertebrate photoreceptors it has been shown that calcium flux is light dependent [16] and that calcium is an important agent in controlling membrane conductance [17] (see Stieve 1981). Pharmacological agents activating adenylate cyclase injected in Limulus photoreceptors induced depolarizations similar to light induced changes in membrane potentiaI (Fein and Corson 1981;see also Fein and Szuts 1982). Invertebrate rhodopsin can activate bovine PDE ) and a native GTPase (Calhoon et al 1980, Vandenberg andMontal 1982).…”
Section: Receptor Potentialmentioning
confidence: 91%